The development of ACP in New Zealand: the roll the National ACP Cooperative. Issue 2 (1st June 2012) - Manson, L.; Snow, B.; Grundy, K.; Read, T.; Rishworth, S.; Leigh Moore, Mary; Daltrey, J.; Naish, M.
Abstract : The development of ACP in New Zealand (NZ) has been driven by clinicians through the National ACP Cooperative (Cooperative). The effective development and deployment of ACP services in NZ requires a national effort to ensure that services are consistent and that they best meet the needs of all people. In the absence of a central government initiative, the Cooperative was formed by clinicians to facilitate this effort. The Cooperative is working to develop a common understanding, framework and direction for ACP in all areas of health. It now works with government and non-governmental agencies, particularly the Ministry of Health, to advance its aims and objectives within the current legal and ethical context in a manner that is coordinated, evidence-based and outcomes focussed. The Cooperative's goals include (1) full community engagement (public and private organisations, Non Government Organisations, networks and the general public) in the design and implementation of ACP; (2) to develop training for health care workers; (3) to grow and support a group of ACP-trained clinicians; (4) to create and control consistency in ACP documentation and to ensure a national mandate for universal documentation and policy development; (5) to influence research on issues related to ACP; and (6) to provide input into and impetus for IT integration. The lessons learnt include the need to focus, grab attention by using stories, engage and to take action. The Cooperative model of ACP development is unique in that it is a clinically-led initiative which transcends organisational boundaries.